Agronomic behaviour and technological evaluation on triticale genotypes for the state of São Paulo, Brazil, in 1988-89 - Felicio, João Carlos; Camargo, Carlos Eduardo de Oliveira; Pizzinatto, Antenor; de Castro, Jairo Lopes; Gallo, Paulo Boler (Pesquisa Agropecuaria Brasileira, 1993)
Twenty three triticale cultivars plus two wheat cultivars were evaluated at different locations of the State of São Paulo, Brazil, during the period 1988-89. Grain yield, hectolitric weight (HW), weight of 1,000 grains, and the simple correlation between these parameters, resistance to diseases and bread qualities were also evaluated. The triticale cultivars Nutria 440, Tarasca 87, Nutria 7272 and IAC 1 showed high regional adaptation. The wheat cultivar IAC 21 presented a high value for hectolitric weight differing from the triticale cultivars, but for the weight of 1,000 grain this wheat cultivar did not differ from the Nutria 440, Nutria 7272 and IAC 21 triticale cultivars, and from the IAC 60 wheat cultivar. The Nutria 440, Tarasca 87, ICT 8804, Cananea 79, ICT 8709 and ICT 8801 triticale cultivars exhibited resistance to leaf rust. All triticale and wheat cultivars under study showed susceptibility to Helminthosporium sp. Considering the technologic evaluation, ICT 8803 exhibited good performance, showing a specific volume of 17,7% superior in relation to the wheat IAC 60, used as control.